Battisi goat: a lesser known goat population of northern India - A.K. Mishra; Amod Kumar; Reena Arora; Avnish Kumar Bhatia; Avneesh Kumar (Journal of Livestock Biodiversity, 2025)
The present study was undertaken to characterize a lesser-known goat population of Uttar Pradesh popularly known as Battisi. It is a dual type goat inhabiting Mathura district of UP and bordering areas of Rajasthan and Haryana. Battisi animals are medium to large in size. The white coat color with black or brown patches on face, abdomen and legs are the important characteristics of Battisi goat. The nose line is typical Roman type. Ears are medium to large in size and the length ranged from 8 to 25 cm. The average adult body weight of males and females’ animals were 45.58 ±4.19 and 35.68 ± 0.65 kg, respectively which varies from 38 to 61.4 kg in males and 28 to 48 kg in females. The overall body length, height, chest girth, face length, face width, ear length and tail were 71.73 ±0.77, 80.42 ±0.76, 79.83 ±0.66, 21.69 ± 0.23, 14.12± 0.14, 20.77 ± 1.14 and 13.79 ± 0.44 cm, respectively. Body weight of lambs in the age groups of 1-3, 3-6 and 9.12 months ranged between 7-33, 22-30 and 22-74 kg respectively. The goats are primarily maintained on grazing (extensive system) with zero input. Goat rearing constituted a vital component of livelihood security and economy of the farmers maintaining this goat population. Majority of the farmers have been rearing this population for more than 30-40 years. The primary study reveals that the Battisi goat is phenotypically different from other registered goat breeds of the region.